2008
DOI: 10.1007/s00423-008-0299-1
|View full text |Cite
|
Sign up to set email alerts
|

Intrathyroidal hematopoiesis: a rare histological finding in an otherwise healthy patient and review of the literature

Abstract: Isolated extramedullary hematopoiesis seems to be more frequent in the thyroid gland than metaplastic bone formation with hematopoiesis, particularly in older people with underlying hematologic disorders. It also represents an important differential diagnosis of anaplastic carcinoma of the thyroid, particularly in intra-operative frozen sections and fine-needle aspiration biopsy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 10 publications
0
9
0
Order By: Relevance
“…Clotting abnormalities were not detected, neither anemia nor hematological disease. Of interest would be the relatively increased frequency of reported cases with intrathyroid hematopoiesis (associated with myelofibrosis or anemia or not) as compared to that of thyroid bone metaplasia [ 10 ]. The extensive study of the quasi-totality of thyroidectomy specimens revealed numerous ossification foci (more than 10) in two of the cases, while hematopoietic elements without bone formation lacked.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Clotting abnormalities were not detected, neither anemia nor hematological disease. Of interest would be the relatively increased frequency of reported cases with intrathyroid hematopoiesis (associated with myelofibrosis or anemia or not) as compared to that of thyroid bone metaplasia [ 10 ]. The extensive study of the quasi-totality of thyroidectomy specimens revealed numerous ossification foci (more than 10) in two of the cases, while hematopoietic elements without bone formation lacked.…”
Section: Discussionmentioning
confidence: 99%
“…Thyroid HBF, frequently designated as bone metaplasia, occurs rarely in the thyroid, being reported both in goiter and in tumors such as adenomas and carcinosarcomas [ 1 10 ]. To our knowledge, seven cases of thyroid sporadic goiter with complete, adult HBF are reported in the English medical literature [ 2 , 4 , 7 10 ]. Here we report five additional cases of complete, adult HBF occurring in the context of sporadic thyroid nodular goiter.…”
Section: Introductionmentioning
confidence: 99%
“…Nodular hyperplasia has the most reported cases of findings of these pathologic processes [2], [3], [4], [5], [6], [7], [8]. The reported cases had varied combinations of these pathologic findings (see Table 1), with most suggesting the aid of bone morphogenic proteins (BMPs) in OM and EBF.…”
Section: Discussionmentioning
confidence: 99%
“…These nodules can undergo hemorrhagic, cystic, and fibrotic changes, and rarely will calcify or ossify. Cases of multinodular goiter, thyroid hyperplasia, follicular adenoma, papillary thyroid carcinoma, and anaplastic thyroid carcinoma have been reported with histopathologic findings of osseous metaplasia (OM), bone marrow metaplasia (BMM), ectopic bone formation (EBF), ossification, and extramedullary hematopoiesis (EMH) [2], [3], [4], [5], [6], [7], [8], [9], [10], [11]. These cases are exceedingly rare.…”
Section: Introductionmentioning
confidence: 99%
“…Thyroid diseases are benign or malignant disorders that affect the structure and function of the thyroid gland [5]. Thyroid histopathology typically shows hemorrhage, fibrosis, calcification, and cystic changes [6].…”
Section: Discussionmentioning
confidence: 99%